Asuhan Keperawatan Keluarga Dengan Gastritis - Penny Oktoriana; Lucia Firsty Puspita Krishna (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
The family is two or more people, individuals who are interdependent with each other to a variety of support, including emotional and economic support the family is the smallest unit of society and as a recipient of nursing care, for that family health care is needed to help improve public health. Currently, public health problems can be caused by habits such as junk food, spicy and sour foods, gas-containing foods, and irregular eating. This can cause diseases, one of which is Gastritis. To be able to overcome problems in families with gastritis, nurses can provide comprehensive nursing care using a nursing process where nurses have an important role in the aspects of promotive, preventive, curative, and rehabilitative.